Investigation of wing clappers for micro-air vehicle - Ho, Aaron Kiu Hieng (2015)
An experimental study was conducted to assess the aerodynamic benefits of using ‘Clap-and-Fling’ flapping flight mechanics for the development of Micro-Aerial Vehicle (MAV). The overall flight performance in terms of thrust generation of the ‘Clap-and-Fling’ flight was compared with the ‘no-clap’ flight in order to distinguish the effect of ‘clapping’ wings for flapping flight applications. The comparison was tested for both wing stroke angle of 65° and 100° respectively to identify the effect of wing amplitude angle on the efficiencies of Clap-and-Fling configuration. The experimental results clearly revealed that the ‘Clap-and-Fling’ mechanics provided significant aerodynamic benefits. The thrust/frequency ratio and the thrust/power ratio is higher for the ‘Clap-and-Fling’ flight. It was found out that the ‘clapping’ effect is significantly dominant in flapping frequency above 20Hz for the 65° stroke angle model. For flapping at 100° wing stroke angle, external factors such as motor overloading and wing stiffness had override the desired ‘clapping’ effect.